Migracja danych do zintegrowanego systemu bibliotecznego udostępnionego na licencji publicznej (open source). Dotychczasowe doświadczenia (przeł. Tomasz Olszewski). - Vandana Singh (Biblioteka)
The present article describes and discusses the aspects of structuring a library collection in an academic library. Direct and indirect actions aimed at improving the acquisitions policy at Docklands Library, one of the three libraries comprising the East London Library, are presented. The most important factors influencing acquisition at this, as well as other academic libraries, include: user’s needs, budget, research mission of the university, and envisaged tendencies in the development of academic disciplines. In conclusion, the author identifies the role of the library as a center whose mission is to maintain the highest possible substantive level of its book collection and provided services.